﻿Extending the diversity of the bryoflora in Kachin amber (Myanmar), with the description of Radula patrickmuelleri, sp. nov. and R. tanaiensis, sp. nov. (Jungermanniopsida, Porellales, Radulaceae) - Kathrin Feldberg; Alfons Schäfer-Verwimp; Ya Li; Matt A. M. Renner (Fossil Record, 2022)
The most prolific source of exquisitely preserved bryophyte fossils is amber, which often contains inclusions in a three-dimensional and life-like state of preservation. In recent years, many fossil species have been described from 16 worldwide deposits ranging in age from the Miocene to the Cretaceous. One of the oldest is mid-Cretaceous Kachin amber from Myanmar. It includes the moss genera Vetiplanaxis and Calymperites as well as the leafy liverwort genera Frullania, Gackstroemia, Protofrullania, and Radula. All liverwort fossils belong to the mainly epiphytic Porellales, a group which was probably strongly influenced by the rise of angiosperms and underwent significant lineage turnover in the Cretaceous. Hence, Kachin amber provides important information on the evolution of leafy liverworts during a period characterized by fundamental changes in terrestrial ecosystems. Here, we describe two new species of the mainly epiphytic leafy liverwort genus Radula (Radulaceae), R. patrickmuelleri sp. nov. and R. tanaiensis sp. nov., and emend the description of Frullania kachinensis (Frullaniaceae). Radula is now represented by four species and one fossil only described to genus level, which indicates a high diversity already in the mid-Cretaceous. Furthermore, we describe additional fossil specimens of Frullaniaceae, including the third fertile specimen of Frullania baerlocheri, one sterile fossil of F. cretacea, and 12 sterile fossils of Protofrullania cornigera. The new fossil evidence necessitates an emendation of a recently published determination key for Cretaceous Jungermanniidae.